Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Could someone verify this proof? Prove $\lim\limits_{n\to\infty} C_n = \lim\limits_{n\to\infty} \dfrac{4n+3}{7n-5} = \dfrac{4}{7}$

Proof: Let $\epsilon > 0$ and take $N = \dfrac{41}{49\epsilon} + 1$ This implies that for all $n > \dfrac{41}{49\epsilon} + 1 \iff n-1 > \dfrac{41}{49\epsilon} \iff \epsilon(n-1) > \dfrac{41}{49} \iff \epsilon > \dfrac{41}{49n - 49} \iff$

$ \iff \epsilon > \dfrac{41}{49n-35} \iff \epsilon > \dfrac{28n+21-28n+20}{49n-35} \iff \dfrac{7(4n+3)-4(7n-5)}{7(7n-5)} \iff \epsilon > \dfrac{4n+3}{7n-5}-\dfrac{4}{7} \iff \epsilon >|\dfrac{4n+3}{7n-5}-\dfrac{4}{7}|$

End of proof

share|cite|improve this question
up vote 2 down vote accepted

This is correct I guess, but extremely tedious. I would never actually prove a limit exists this way when we are dealing with quotients of polynomials. The standard thing to do is prove the following theorem:

Theorem. If $\lim\limits_{n \to \infty} a_n = A$ and $\lim\limits_{n \to \infty} b_n = B$ and $c\in \mathbb{R}$ then $$ \lim\limits_{n \to \infty}(c a_n) = c A \text{ as long as $cA \neq 0 \cdot \infty$} $$ $$ \lim\limits_{n \to \infty}(a_n + b_n) = A + B \text{as long as $A + B \neq \infty - \infty$} $$ $$ \lim\limits_{n \to \infty}(a_n b_n) = AB , \text{ as long as $AB \neq 0\cdot \infty$} $$ $$ \lim\limits_{n \to \infty}\frac{a_n}{b_n} = \frac{A}{B}, \text{ as long as $B \neq 0$ and not $B=A=\infty$}. $$

One you have this theorem we can write $$\frac{4n+3}{7n-5} = \frac{4 + \frac{3}{n}}{7 - \frac{5}{n}}$$ for all $n \neq 0$. Applying the quotient of limits part of the previous theorem we find $$ \lim_{n \to \infty}\frac{4n+3}{7n-5} = \lim_{n \to \infty}\frac{4 + \frac{3}{n}}{7 - \frac{5}{n}} = \frac{\lim\limits_{n \to \infty}(4+\frac{3}{n})}{\lim\limits_{n \to \infty}(7 - \frac{5}{n})} = \frac{4+0}{7+0} = \frac{4}{7}. $$

share|cite|improve this answer

I would work forwards, not backwards starting with magic constants.

We want to show that $lim_{n \to \infty} \frac{4n+3}{7n-5} = \frac{4}{7}$.

$\frac{4n+3}{7n-5} - \frac{4}{7} = \frac{7(4n+3)-4(7n-5)}{7(7n-5)} = \frac{28n+21-28n+20}{49n-35} = \frac{41}{49n-35} $.

To make this to be less than $c$ for any real $c$, choose $n$ such that $\frac{41}{49n-35} < c$ or $41 < 49cn-35c$ or $n > \frac{41+35c}{49n}$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.